2011
DOI: 10.1038/tp.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Association of a MET genetic variant with autism-associated maternal autoantibodies to fetal brain proteins and cytokine expression

Abstract: The contribution of peripheral immunity to autism spectrum disorders (ASDs) risk is debated and poorly understood. Some mothers of children with ASD have autoantibodies that react to fetal brain proteins, raising the possibility that a subset of ASD cases may be associated with a maternal antibody response during gestation. The mechanism by which the maternal immune system breaks tolerance has not been addressed. We hypothesized that the mechanism may involve decreased expression of the MET receptor tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 60 publications
1
64
0
Order By: Relevance
“…For example, MET signaling induces a tolerogenic phenotype in dendritic cells without affecting their antigen presenting capabilities (Okunishi et al, 2005; Rutella et al, 2006). We recently showed that the MET ‘C’ variant predisposes to innate immune cell activation and the loss of self-tolerance (Heuer et al, 2011). Individuals with a functional polymorphism in the promoter for MET, namely rs1858830 ‘C’ allele, carry a 2.25 fold increased relative risk for autism (Campbell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MET signaling induces a tolerogenic phenotype in dendritic cells without affecting their antigen presenting capabilities (Okunishi et al, 2005; Rutella et al, 2006). We recently showed that the MET ‘C’ variant predisposes to innate immune cell activation and the loss of self-tolerance (Heuer et al, 2011). Individuals with a functional polymorphism in the promoter for MET, namely rs1858830 ‘C’ allele, carry a 2.25 fold increased relative risk for autism (Campbell et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper sheds insight into how the maternal immune system may lose tolerance which would allow it to produce antibodies against the fetal brain. The MET promoter variant rs1858839C allele was found to be significantly associated with the presence of ASD-associated maternal autoantibodies against fetal brain proteins [57]. MET receptor tyrosine kinase plays a role in negative regulation of the immune response and a disruption in this regulation could explain why there is a break in maternal tolerance to the fetus that leads to the production of autoantibodies.…”
Section: Findings Referencesmentioning
confidence: 98%
“…Recent estimates at this site suggest that the CC and CG alleles represent a 1.76 and 1.59 relative risk, respectively, over the GG allele (Campbell et al, 2008), with an odds ratio of 1.64 for the C variant (Jackson et al, 2009). This MET variant also appears connected to both an increase in 37/73 kDa maternal autoantibodies and a decrease in maternal IL-10, suggesting another mechanism through which MET may associate with ASD as a susceptibility factor (Heuer et al, 2011).…”
Section: Immunogenetic Factorsmentioning
confidence: 99%